BIOLEACHING OF LOW GRADE NICKEL ORE USING INDIGENOUS FUNGI - Sri Handayani; Suratman Suratman (Puslitbang tekMIRA, 2016)
In this research, the biological leaching of nickel by indigenous fungi isolated from Indonesian limonite was studied to develop a feasible technique for microbial recovery of nickel from low grade nickel ore. XRD analyses indicated that goethite, alumina and quartz were major mineral composition of the ore. In the present study, isolated fungal strains having potential to solubilize nickel were characterized. that were identified as Aspergillus sp and Penicillium sp depending upon their colony morphology and microscopic studies. All microorganisms found were tested for organic acid production and leaching capabilities of nickel. Leaching experiments were performed in 250 ml Erlenmeyer flask at room temperature and 150 rpm agitation under aseptic conditions. It was observed that the Aspergillus sp substantially leached more nickel from limonite compared to the Penicillium sp. Nickel solubilization was related to pH decrease and organic acid excreted caused by growth of fungi in medium containing glucose as carbon source. The mechanisms of nickel extraction had been examined either directly or indirectly related to fungal activity. The presence of fungal cells seems to improve the leaching process. However, the use of higher pulp density resulted in a decrease of nickel solubilization. The maximum nickel recovery was 57% at 5% pulp density after 20 days of direct leaching by Aspergillus sp.